Improving thermal performance of existing uninsulated R.C. domes through passive cooling measures using polyurethane foam in double skin layer in hot climate. (June 2022) - Binyaseen, Adel M.
Abstract: Thermal insulation is a significant issue of building sustainability. Facades and roofs represent the exterior envelop of buildings. One of the weakest points in roof insulation is dome. Most of the domes in Saudi Arabia are thermally uninsulated due to the absence of practical insulation techniques. This paper concerns solving the problem of thermally uninsulated R.C. domes. A selected zone in Al-wali district in Makkah has around 68 thermally uninsulated R.C. domes made of 150 mm R.C. dome roof, 25 mm mortar layer with acrylic thermal emulsion paint from outside, and 3 mm gypsum plastering from inside. This construction has low thermal resistivity value (U-value = 10.3627 W/m 2 K) exceeding region code of 0.31 W/m 2 K. Three options were tested on three similar uninsulated domes. Firstly, creating 50 mm foam concrete layer covered by light acrylic ceramic microspheres-based for weather protection, an option that has been widely used by most owners. Secondly, creating 75 mm polyurethane foam layer covered by acrylic ceramic microspheres-based paint, an option that has difficulty in external cladding, maintenance, and aesthetic value. Thirdly, creating double-skin layer reinforced by 220 mm vertical steel bars, consisting of 75 mm polyurethane foam with an external cladding of 6 mm ceramic tiles, an option suggested by this paper based on most owners' preferences since it controls heat transfer and allows external cladding. Difference in temperature (ΔT) between inside and outside the three treated domes were reported using surface infrared laser thermometer. Option 1 was practical and economical, but ineffective (U-value =2.5445 W/m 2 K, ΔT= 5.8 ֯C). Options 2& 3 were almost similar, both were effective and satisfy area code (U-value =0.2949, 0.2920 W/m 2 K, ΔT= 14.3, 14.8 ֯C respectively). Highlights: The study concerns with solving the problem of thermally uninsulated R.C. domes. Three options were suggested to improve thermal resistivity. These are adding foam concrete layer, adding polyurethane layer, and using polyurethane in double skin layers strengthened by vertical steel bars. Option1, owners' common solution, was ineffective. Option 2 was effective but with maintenance and architectural difficulties. Option 3 is the paper's suggestion to owners as it is effective and allows external cladding.